LIQUIDITY DETERMINANTS OF SHARIA COMMERCIAL BANKS IN INDONESIA - Laylan Syafina (CERED Indonesia Institute, 2021)
This research aims to determine whether the Capital Adequacy Ratio (CAR), Return on Assets (ROA), Return On Equity (ROE) and Firm Size partially and simultaneously affect liquidity as stated by the Financing to Deposit Ratio (FDR). This type of research is quantitative with a descriptive approach. The data analysis technique used SPSS 22 software. The tests in this study were the classical assumption test, multiple regression analysis, and hypothesis testing. The results showed that partially the Capital Adequacy Ratio (CAR), Return on Assets (ROA), and Return On Equity (ROE) had no effect on the Financing to Deposit ratio (FDR) while Firm Size partially had a negative and significant effect on Financing. to Deposit ratio (FDR). Simultaneously, Capital Adequacy Ratio (CAR), Return on Assets (ROA), Return On Equity (ROE), and Firm Size have a joint and significant influence on the Financing to Deposit ratio (FDR).